Uniformity Instrument Evaluation Materials with Excretion System Materials that Given by Teacher All The Time Learning Process in SMA Kota Bandung - Sepita Ferazona (Bioeducation Journal, 2017)
The evaluation instrument in measuring of student ability must be appropriate with the basic competence, so that the expected competence can be achieved. This research is seen from the conformity of evaluation instrument material aspect with the material presented by teacher during the learning process in the classroom. The method that used in this research is descriptive method. The research’s subject were ten biology teachers, from seven SMAN in Bandung as a sample, each school representing tree clusters. The selection of the sample is done by using “startified sampling” technique, that is by choosing school with high category, medium and low. The basic competence analyzed is the material of excretion system class XI. The date were obtained by observation, documentation study and questionnaire. Conformity of evaluation instrument material with indicator in RPP that is 82,38%. While the conformity of evaluation instrument material with the material contained in the basic competence is 72,30%. While the conformity of evaluation instrument material with the material who presented by teacher during the learning process in the clasroom is 79,83%.